Directing film techniques and aesthetics - Rabiger, Michael; Hurbis-Cherrier, Mick (Routledge, 2020)
The accompanying companion website includes film analysis exercises, shooting projects, checklists and assignment forms, analytical questionnaires, updated production forms and logs for all phases of a project with links to additional resources and set safety advice"--